2011
DOI: 10.1080/15287394.2011.595669
|View full text |Cite
|
Sign up to set email alerts
|

Fibrogenic and Redox-Related but not Proinflammatory Genes are Upregulated in Lewis Rat Model of Chronic Silicosis

Abstract: Silicosis, a fibrotic granulomatous lung disease, may occur through accidental high-dose or occupational inhalation of silica, leading to acute/accelerated and chronic silicosis, respectively. While chronic silicosis has a long asymptomatic latency, lung inflammation and apoptosis are hallmarks of acute silicosis. In animal models, histiocytic granulomas develop within days after high-dose intratracheal (IT) silica instillation. However, following chronic inhalation of occupationally relevant doses of silica, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 48 publications
2
11
0
Order By: Relevance
“…Langley et al found that CCL2 and CCL7 were persistently upregulated in rat lungs exposed to inhaled crystalline silica, a dust with high toxicity [32]. Fujita et al also reported that CCL2 and CCL7 were upregulated in the lungs of rats injected intratracheally with in ammogenetic SWCNT [27,33].…”
Section: Discussionmentioning
confidence: 99%
“…Langley et al found that CCL2 and CCL7 were persistently upregulated in rat lungs exposed to inhaled crystalline silica, a dust with high toxicity [32]. Fujita et al also reported that CCL2 and CCL7 were upregulated in the lungs of rats injected intratracheally with in ammogenetic SWCNT [27,33].…”
Section: Discussionmentioning
confidence: 99%
“…SPP1 contributes to human fibrotic lung disease, and increases in SPP1 are associated with pulmonary fibrosis ( Foster et al 2015 ; Nau et al 1997 ; Pardo et al 2005 ) and with the development of fibrosis in a number of animal models ( Berman et al 2004 ; Langley et al 2011 ; Ma et al 2012 ; Mangum et al 2004 ; Miyazaki et al 1995 ; Oh et al 2015 ; Sabo-Attwood et al 2011 ; Takahashi et al 2001 ). For example, bleomycin treatment of mice results in an increase in SPP1 mRNA and protein at 14 days post-exposure, and treatment with an antibody that blocks SPP1 function partially protects against fibrosis development ( Takahashi et al 2001 ).…”
Section: Discussionmentioning
confidence: 99%
“…SPP1 also mediates fibroblast migration through integrin- ( Anwar et al 2012 ; Li et al 2000 ) and matrix metalloproteinase–dependent mechanisms ( Lund et al 2009 ). Lung SPP1 increases in humans with pulmonary fibrosis ( Foster et al 2015 ; Nau et al 1997 ; Pardo et al 2005 ) and in mouse ( Berman et al 2004 ; Miyazaki et al 1995 ; Oh et al 2015 ; Sabo-Attwood et al 2011 ; Takahashi et al 2001 ) and rat ( Langley et al 2011 ; Ma et al 2012 ; Mangum et al 2004 ) models of pulmonary fibrosis. In addition, SPP1 may be a useful biomarker for the development and progression of fibrotic lung diseases ( Boon et al 2009 ; Kadota et al 2005 ; Kelly et al 2006 ; O’Regan et al 2006 ; Pardo et al 2005 ; Selman et al 2006 ; Vij and Noth 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…According to the literature, increasing evidence shows that lung inflammation and apoptosis are hallmarks of acute silicosis 14 ) . In animal models of acute silicosis, severe lung inflammation, alveolar lipoproteinosis, apoptosis, induction of reactive oxygen species, production of proinflammatory cytokine/chemokine, and tissue destruction were found 14 ) . The accelerated acute inhalation model also led to the development of acute-like injury (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…apoptosis, inflammation, tissue destruction) 15 ) . Animal models have shown that genes regulating fibrosis, oxidative stress, and metalloproteases contribute to both acute and chronic silicosis, but proinflammatory cytokines are associated with acute but not chronic silicosis 14 ) .…”
Section: Discussionmentioning
confidence: 99%